A comparative analysis of the chemical nature of defensive secretions of Gonyleptidae (Arachnida : Opiliones : Laniatores) - Hara, M. R.; Cavalheiro, Alberto José [UNESP]; Gnaspini, P.; Santos, DYAC (Elsevier B.V., 2005)
The arachnids of the order Opiliones (harvestmen) produce substances used in defense. In the present paper, we analyzed 22 species of Gonyleptidae to explore the use of defensive substances in taxonomy and evolutionary biology. Thirty-seven different compounds were detected, 18 of which were preliminarily identified. These compounds were mapped onto a phylogenetic tree showing the relationships within the Gonyleptidae. Data from Cosmetidae were used as an outgroup. Five ketones and six alkyl phenols were reported for the first time in harvestmen. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Opiliones; Gonyleptidae; harvestmen; chemical defense; chemical secretion; quinones; phenols; ketones